Improvement of Sustainability Strategy toward Environmental Performance Assessment: Case Study of PT ABC - Kresna, Alfi Zulfiandra; Hermawan, Ancella Anitawati (E-Jurnal Akuntansi; Vol 35 No 3 (2025)DO - 10.24843/EJA.2025.v35.i03.p16, 2025)
The research aims to analyze the company's sustainability strategy regarding environmental aspects, and whether it has been implemented. This research use a case study research for problem solving with the research’s object PT ABC, a logistic company. The results of the 2023 assessment by independent institutions and the Government agency, BPKP showed a poor grade for environmental aspect. Data collection used document analysis and interviews.  The research was carried out by assessing the company's sustainability strategy using Integrated Port Management (IPM) and comparing it with the results of independent assessments. The results show the company has implemented environmental aspects according to IPM, while monitoring and evaluation have not been carried out and its environmental work programs have not been disclosed. The research recommends that companies develop a roadmap for implementating their environmental programs, as material for evaluation and monitoring and to reveal the realization of their work program in their sustainability report.  Keywords: Sustainable Strategy; Environmental Performances; Integrated Port Management